1969
DOI: 10.1037/h0027311
|View full text |Cite
|
Sign up to set email alerts
|

Optimal behavior in free-operant experiments.

Abstract: Expected Utility Theory successfully predicts the steady-state relative frequencies of the two alternatives in two-key, discrete-trial probability-learning experiments, in concurrent variable interval schedules, and in concurrent variable interval schedules modified to study magnitude and delay of reinforcement and conditioned reinforcement. It also successfully predicts the relative frequencies of interresponse times in one-key variable interval schedules. Different interresponse times between pecks on a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
141
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(148 citation statements)
references
References 50 publications
(48 reference statements)
5
141
1
Order By: Relevance
“…In the literature on operant behavior, such a view is referred to as "molar", to distinguish it from "molecular" analysis, which is concerned with moment-tomoment decisions. Shimp (1969) claimed that momentary maximization of the probability of reward on VI schedules would result in matching. We believe that Shimp's use of the term 'optimal' in this context has led to an unwarranted opposition between molar (i.e., global) and molecular (i.e., immediate or momentary) maximization.…”
Section: Discrete Trial Conc VI Vi Immediate and Overall Maximizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature on operant behavior, such a view is referred to as "molar", to distinguish it from "molecular" analysis, which is concerned with moment-tomoment decisions. Shimp (1969) claimed that momentary maximization of the probability of reward on VI schedules would result in matching. We believe that Shimp's use of the term 'optimal' in this context has led to an unwarranted opposition between molar (i.e., global) and molecular (i.e., immediate or momentary) maximization.…”
Section: Discrete Trial Conc VI Vi Immediate and Overall Maximizationmentioning
confidence: 99%
“…Immediate Maximization Shimp (1969) suggested that organisms should behave optimally in the sense of always making the choice that momentarily has the greatest expected value. This principle is known as immediate or molecular maximization.…”
Section: Discrete Trial Conc VI Vi Immediate and Overall Maximizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several "molecular" or "quasi-molecular" accounts of matching, which posit maximizing payoffs at a local or molecular level, have been proposed. For example, meloriation (Herrnstein & Vaughan, 1980;Vaughan, 1985) and "momentary maximizing" (Shimp, 1969) argue that subjects choose the better of two local rates or probabilities of reinforcement, and this results in overall matching. Rather than explaining it, other, "molar" matching accounts simply assume matching (e.g., Baum & Rachlin, 1969; Gallistel, 1990;Mark & Gallistel, 1994).…”
mentioning
confidence: 99%
“…Skinner's "kinds of evidence" for strength -including whether a response is emitted at all, its energy level, its speed, the amount of repetition, and its overall frequency -suggest that strength is a property underlying observed behavior. Constructions such as "evidence of strength," "sign of strength," and "indicator of strength" occur at least 15 times in Verbal Behavior, making strength come across as a kind of "state variable" which is not directly observable (Shull, 1993) Shimp, 1969), stimulus generalization (e.g., Migler, 1964), and so-called continuous repertoires (Wildemann & Holland, 1972).…”
mentioning
confidence: 99%